PERTIMBANGAN HAKIM PADA PUTUSAN NOMOR 458/PDT.SUS-PKPU/2021/PN.NIAGA.JKT.PST TERHADAP PROSES TERJADINYA PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG - Sari, Raden Ayu Widya; Oktalia, Sari; Elmer, Evien; Sigit, Kgs M Lukman; Siregar, Josua Martua (Lex Stricta : Jurnal Ilmu Hukum, 2023)
Abstract The PKPU application can be submitted before or after the bankruptcy application. The aim of PKPU itself is to achieve peace between debtors and all creditors. However, if the peace plan is not achieved or the court rejects the peace plan, the court is obliged to declare the debtor bankrupt. The research method in this writing is normative legal research with empirical material. The results of research into the judge's considerations in decision Number 458/Pdt.Sus-PKPU/2021/PN.Niaga.Jkt.Pst regarding the PKPU process are actions based on the law and his beliefs as a judge, considering all the factors contained in the existing trial facts carefully. juridical, sociological and philosophical assessments. Meanwhile, the legal consequences of the appointment of administrators are causing legal action from the debtor in PKPU, regarding the debtor's debt in PKPU, reciprocal agreements, handover of debtor's goods, rental agreements, work agreements, legal consequences for ongoing cases against debtors in PKPU, for debt set-offs. , and towards debtor participants and debt guarantors. Recommendation, Judges need to master the issues and legal basis for resolving problems, judges' understanding of knowledge outside of law such as economics, business, accounting is very necessary to resolve PKPU disputes. Apart from that, there is a need for outreach or general seminars, especially for the general public or entrepreneurs, related to the field of bankruptcy and PKPU. Keywords: PKPU, Management, Legal Consequences, Judge's Consideration.